MODEL PENDIDIKAN ISLAM BERBASIS SENI SALAWATAN - Rido Kurnianto (Universitas Muhammadiyah Ponorogo, 2014)
This research is done based on the context of Islamic education which it has been done too by the group of Salawatan Khataman Nabi. The interested fact is that the art of salawatan Khataman Nabi at Kauman Ponorogo led by mr.Mashuri not only successfully existed the traditional art, but also has educated people in Islamic education by applying this kind of art. This reseach is done to identify the model of Islamic education based on the art of Salawatan Khataman Nabi. The technic of data collection that used in this reseach is the collaboration between observation, documentation and deep interview to get complete data about the model of Islamic education done by the art of Salawatan Khataman Nabi at Ponorogo. The collected data in this reseach analized qualitatively before entering to the step of analisis the collected data is organized as well. In the step of organizing data it was edited systematically. It proposed to accomplish,explain and seek the relevant of data and the focus of this research found the bases of discovery about model of Islamic education based on the Salawatan Khataman Nabi, that contained of four models as follows: (1) the model of phoetry understanding in Javanese language; (2) the model of members awareness based on the ideal of their chief; (3) the model of continuited brotherhood relationship; and (4) the model of entertainment